Molecular Biology of Disease Vectors - Kotsyfakis, Michail (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Arthropod disease vectors transmit not only serious diseases, such as malaria, but many other diseases as well, many of which are neglected to various extents. In most cases, a tripartite interaction is involved between the arthropod disease vector, the vertebrate host, and the vector-borne pathogens. The reprint aims to present a selection of the latest data (and up to date information in the case of reviews) about the molecular and biochemical events that mediate this tripartite interaction with emphasis on ticks and mosquitoes.